Community-level Association between Clinical Trachoma and Ocular Chlamydia Infection after MASS Azithromycin Distribution in a Mesoendemic Region of Niger. (4th July 2019) - Amza, Abdou; Kadri, Boubacar; Nassirou, Beido; Cotter, Sun Y; Stoller, Nicole E.; West, Sheila K; Bailey, Robin L.; Porco, Travis C.; Keenan, Jeremy D.; Lietman, Thomas M.; Oldenburg, Catherine E.
ABSTRACT: Purpose : The clinical sign trachomatous inflammation – follicular (TF) is used to monitor indication for and response to mass azithromycin distribution in trachoma-endemic communities. Here, we assess the relationship between TF, trachomatous inflammation – intense (TI), and infection with ocular Chlamydia trachomatis over time during annual mass azithromycin distribution. Methods : We used data from a cluster-randomized trial of mass azithromycin distribution for trachoma control in a mesoendemic region of Niger. This study includes 24 communities that received 3 years of annual mass azithromycin distribution. TF, TI, and ocular chlamydia infection were monitored among children aged 0–5 years. We assessed the correlation between the prevalence of ocular chlamydia infection and 1) TF and 2) TI prevalence over time. Results : At baseline, ocular chlamydia prevalence was 21.2% (95% CI 14.3–28.1%), TF prevalence was 27.7% (95% CI 21.2–34.2%), and TI prevalence was 8.3% (95% CI 5.2–11.5%). The prevalence of all three measures decreased significantly over time (P < 0.001). At baseline, ocular chlamydia infection prevalence was strongly correlated with both TF (rho = 0.78, P < 0.0001) and TI (rho = 0.76, P < 0.0001). The correlation between ocular chlamydia infection and both TF and TI was weak at months 12 and 24. At 36 months, when TF prevalence had dropped below 10%, ocular chlamydia infection and TF were moderately correlated (rho = 0.70, P = 0.0002). Conclusions : Both TF and TI are good indicators of infection prevalence prior to mass azithromycin distribution. However, this relationship may be affected by repeated rounds of mass azithromycin distribution.